Transient and dynamic DNA supercoiling potently stimulates the leu-500 promoter in Escherichia coli - Zhi, Xiaoduo (J Biol Chem, 2017)
The inactive prokaryotic leu-500 promoter (P(leu-500)) contains a single A-to-G point mutation in the −10 region of the leucine operon promoter, which causes leucine auxotrophy. This promoter can be activated by (−) DNA supercoiling in Escherichia coli topA strains. However, whether this activation arises from global, permanent, or transient, dynamic supercoiling is still not fully understood. In this article, using a newly established in vivo system carrying a pair of divergently coupled promoters, i.e. an IPTG-inducible promoter and P(leu-500) that control the expression of lacZ and luc (the firefly luciferase gene), respectively, we demonstrate that transient, dynamic (−) DNA supercoiling provided by divergent transcription in both wild-type and topA strains can potently activate P(leu-500). We found that this activation depended on the promoter strength and the length of RNA transcripts, which are functional characteristics of transcription-coupled DNA supercoiling (TCDS) precisely predicted by the twin-supercoiled domain model of transcription in which a (+) supercoiled domain is produced ahead of the RNA polymerase and a (−) supercoiled domain behind it. We also demonstrate that TCDS can be generated on topologically open DNA molecules, i.e. linear DNA molecules, in Escherichia coli, suggesting that topological boundaries or barriers are not required for the production of TCDS in vivo. This work demonstrates that transient, dynamic TCDS by RNA polymerases is a major chromosome remodeling force in E. coli and greatly influences the nearby, coupled promoters/transcription.